2003
DOI: 10.1136/gut.52.7.988
|View full text |Cite
|
Sign up to set email alerts
|

Live probiotics protect intestinal epithelial cells from the effects of infection with enteroinvasive Escherichia coli (EIEC)

Abstract: Background: The colonic epithelium maintains a life long reciprocally beneficial interaction with the colonic microbiota. Disruption is associated with mucosal injury. Aims: We hypothesised that probiotics may limit epithelial damage induced by enteroinvasive pathogens, and promote restitution. Methods: Human intestinal epithelial cell lines (HT29/cl.19A and Caco-2) were exposed to enteroinvasive Escherichia coli (EIEC 029:NM), and/or probiotics (Streptococcus thermophilus (ST), ATCC19258, and Lactobacillus ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
348
2
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 555 publications
(380 citation statements)
references
References 43 publications
14
348
2
6
Order By: Relevance
“…Exposure of colonic epithelial cell lines to bacterial lipopeptide or peptidoglycan results in apical tightening and sealing of the tight junctional protein ZO-1 and increased transepithelial electrical resistance (38). These data may tie together previous observations that certain probiotic preparations increased barrier function in vitro (39,40) and attenuate inflammation in animal models of colitis (41)(42)(43). However, in an animal model of necrotizing enterocolitis, LPS inhibited migration of intestinal epithelial cells across a wound through a TLR4-dependent mechanism (44).…”
Section: Homeostatic Function Of Bacterial-epithelial Interactionssupporting
confidence: 57%
“…Exposure of colonic epithelial cell lines to bacterial lipopeptide or peptidoglycan results in apical tightening and sealing of the tight junctional protein ZO-1 and increased transepithelial electrical resistance (38). These data may tie together previous observations that certain probiotic preparations increased barrier function in vitro (39,40) and attenuate inflammation in animal models of colitis (41)(42)(43). However, in an animal model of necrotizing enterocolitis, LPS inhibited migration of intestinal epithelial cells across a wound through a TLR4-dependent mechanism (44).…”
Section: Homeostatic Function Of Bacterial-epithelial Interactionssupporting
confidence: 57%
“…For instance, Resta-Lenert & Barrett (2003) have shown that the probiotics Streptococcus thermophilus and Lactobacillus acidophilus protect epithelial cells (HT-29 and Caco-2) against enteroinvasive E. colimediated disruption of epidermal growth factor signalling. Consistent with our results, pre-treatment of epithelial cells with probiotics was required to provide protection against the effects of EHEC on host cell signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, pre-treatment of epithelial cells with probiotics was required to provide protection against the effects of EHEC on host cell signal transduction. In addition, live probiotics are required to ameliorate the adverse effects of pathogens, since neither antibiotic-killed (Resta-Lenert & Barrett, 2003) nor heat-killed ; this study) probiotics prevent the pathogenic effects of E. coli enteropathogens on cultured epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…72 As noted in other studies with prebiotics and probiotics, effects on gut barrier function varied among strains and effector molecules. [73][74][75] While intestinal permeability may be altered in a subset of IBS patients, the relationship with dysbiosis requires further study. Commensal and probiotic organisms can regulate intestinal barrier function through a variety of mechanisms and hence contribute to the development or perpetuation of IBS.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%